A parallel engine for graphical interactive molecular dynamics simulations - Rodrigues, E. R.; Preto, A. J.; Stephany, S. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2004)
The current work proposes a parallel implementation for interactive molecular dynamics simulations (MD). The interactive capability is modeled by finite automata that are executed in the processing nodes. Any interaction implies in a communication between the user interface and the finite automata. The ADKS, an interactive sequential MD code that provides graphical output was chosen as a case study. A parallel version of this code was developed using the MPI communication library to check its parallel performance without/with visualization. Performance results are discussed for both cases and the influence of visualization in the performance is also treated, including image update rate. In order to allow a modular approach, a new parallel version of the ADKS is being implemented employing the PyMPI Python extension.